CAUSES OF SOCIO-ECONOMIC CONFLICTS IN CUSTOMS AND METHODS OF OVERCOMING THEM - A. Andrianov; V. Ovchinnikova (Вестник университета)
The article discusses the concept of the school of human relations as tool for solving situations conflict in the customs authorities. Provides statistics on the results of analysis of the socio-economic conflicts. Ways to overcome the conflict with the customs authorities.